Economic Transition and Health Care Reform : The Experience of Europe and Central Asia - Leive, Adam. (Washington, D.C. : International Monetary Fund, 2010)
This paper exploits the staggered adoption of major concurrent health reforms in countries in Europe and Central Asia after 1990 to estimate their impact on public health expenditure, utilization, and avoidable deaths. While the health systems all derived from the same paradigm under central planning, they have since introduced changes to policies regarding cost-sharing, provider payment, financing, and the rationalization of hospital infrastructure. Social health insurance is predicted to increase this share, although the leads of both social health insurance and primary care fee-for-service suggest endogeneity may be an issue with the outpatient share regressions. Provider payment reforms produce the largest impact on spending, with fee-for-service increasing spending and patient-based payment reducing it. The impact on avoidable deaths is generally negligible, but there is some evidence of improvements due to fee-for-service. Considering the corresponding relative reduction in inpatient admissions and the incentives fee-for-service provides to deliver additional services, perhaps there is an overprovision of services in the primary care setting and an underutilization of more specialized hospital services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet